Síntese do híbrido de óxido de grafeno reduzido/óxido de cobalto a partir de baterias íons-lítio exauridas e suas aplicações eletroquímicas como pseudocapacitor e sensor de ácido ascórbico - Ribeiro, Jessielem Soares (2019)
In this work, hybrid materials based on reduced graphene oxide (rGO) and cobalt oxide (CoO) were synthesized from recycled Li-ion batteries. A hydrometallurgical route was employed in the recycling process, with citric acid and nitric acid used as the leaching agents for the cathode and anode materials, respectively. Graphite oxide (GO) was prepared from the recycled graphite by a modified Hummers method; the hybrid material was produced by mixing GO and the recycled metal oxides (mostly CoO) using a sol-gel route followed by heat treatment at 450 °C during 2 h. The physicochemical characterization of the hybrid material indicated the formation of crystalline CoO (with face centered cubic structure) and rGO (with turbostratic structure), whereas lithium and manganese were also identified as minor components. The electrochemical performance of the hybrid material was evaluated by cyclic voltammetry, galvanostatic charge/discharge cycling and electrochemical impedance spectroscopy. The obtained specific capacitance reached values of 88.5 and 23.01 F g-1 for current densities of 0.07 and 0.2 A g-1, respectively, in the case of the material deposited on a glass carbon electrode. The study of the electrochemical oxidation of ascorbic acid using the hybrid material as electrode showed good linearity in the relationship between the oxidation current and the acid concentration. These results showed that the hybrid material produced from the recycled batteries is promising for applications as supercapacitor and as electrochemical sensor.